2014
DOI: 10.3109/07388551.2014.913548
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoates – what are the uses? Current challenges and perspectives

Abstract: Over the past few decades, a considerable attention has been focused on the microbial polyhydroxyalkanoates (PHAs) owing to its multifaceted properties, i.e. biodegradability, biocompatibility, non-toxicity and thermo-plasticity. This article presents a critical review of the foregoing research, current trends and future perspectives on the value added applications of PHAs in the biomedical, environmental and industrial domains of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 143 publications
0
21
0
Order By: Relevance
“…Polyhydroxyalkanoates (PHAs) have drawn significant attention due to their physico-chemical properties, which is quite similar to that of plastics and the possibility of producing them from biological materials. The demand of PHA is increasing rapidly and is expected to grow to around 34,000 MT by 2018 [1]. At present, the large scale production of these polymers is limited by expensive feeds and costly recovery processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxyalkanoates (PHAs) have drawn significant attention due to their physico-chemical properties, which is quite similar to that of plastics and the possibility of producing them from biological materials. The demand of PHA is increasing rapidly and is expected to grow to around 34,000 MT by 2018 [1]. At present, the large scale production of these polymers is limited by expensive feeds and costly recovery processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…PHB, poly(3hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(3hydroxybutyrate-co-4-hydroxybutyrate) (P3HB4HB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHB-HHx), and poly(3-hydroxybutyrate-co-3-hydroxyvalerateco-3-hydroxyhexanoate) (PHBVHHx) are biomaterials that stimulate cell proliferation and tissue regeneration without inducing tumor growth. Experimental studies on rats, dogs and sheep have shown that both PHB and PHBV can act as a scaffolding to regenerating cells of the gastrointestinal tract and blood vessels (Masood et al 2014). For the treatment of nervous system disorders, PHBVHHx appears to be the best of PHAs.…”
Section: Applications Of Polyhydroxyalkanoatesmentioning
confidence: 99%
“…300 species) (Sabbagh and Muhamad 2017;Kosseva and Rusbandi 2018). Production of PHAs in microbial cells is intensified under specific conditions such as the lack of nitrogen, phosphorus, sulfur, potassium, zinc, iron, magnesium or oxygen (Masood et al 2014). PHAs are round shape granules with a diameter of 0.1-0.2 µm which are accumulated in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…So far, eight pathways of PHA biosynthesis have been found out; among which three main pathways were explained in figure 5. [47,48]. Among the microbes, C. necator (involves 3 main enzymes βketothiolase, NADPH-dependent acetoacetyl-CoA reductase and PHA synthase) was investigated to the maximum extent.…”
Section: Types Of Phamentioning
confidence: 99%